Program Perceived Value and Program Satisfaction Influences on Store Loyalty: Insights from Retail Loyalty Progam - Omar, Nor Asiah; Musa, Rosidah; Nazri, Muhamad Azrin (Gadjah Mada International Journal of Business, 2007)
Investigations to determine whether program perceived value could influence program satisfaction, program card loyalty and store loyalty are critical to elucidate the roles and significance of the constructs and advancing management practice. Accordingly, in line with this research direction, this study aims to assess the effects of program perceived value offered by few leading retail superstores and departmental stores in Malaysia on its membersâ loyalty towards the store. The data set utilized in this study has been obtained via quota sampling technique, where a sample of 153 retail loyalty programsâ members was analyzed. An integrative conceptual model was developed and tested using Structural Equation Modeling using AMOS program. The results exemplify that program perceived value is a strong driver of program satisfaction and program card loyalty. Unexpectedly, program perceived value is not a significant predictor of store loyalty but, it has an indirect effect on store loyalty mediated by program satisfaction. Continuous plea in marketing management is to make marketing instruments more efficient. In recent years introduction of customer relationship marketing instruments is strongly advocated, both in marketing theory and practice. Several researchers (e.g., Berry 1983; Berry and Parasuraman 1991; and Gronroos, 1994) have changed the focus of a marketing orientation from attracting short-term, discrete transactional customers to retaining long-lasting, intimate customer relationships. In fact Roberts, Varki, Brodie (2003), further suggested that it is best to describe relationship marketing as the formation of âbondsâ between the company and the customer. Achieving an effective relationship in a consumer context is considered to be even more challenging than it is in a business-to-business context, given the generally more polygamous character of consumers as opposed to business customers (Keng and Ehrenberger 1984; Pressey and Matthews 1998).